Enhancing Elementary Students’ Writing Skills through Multiple Intelligence Strategies: A Case Study - Muhammad Nabil Afis; Widia Nur Jannah; Erna Labudasari (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
In essence, humans are given intelligence in themselves to get the learning they need, especially in language skills in Indonesian subjects in elementary school. This study will discuss the analysis of multiple intelligence strategies on the writing skills of grade III students of elementary school 1 watubelah. This study uses a case study approach with data collection through observation, interviews and documentation. The procedure begins with a diagnosis assessment in understanding the student’s intelligence. The implementation is carried out by treating 8 intelligences according to Howard Gardner’s theory. The results of the study showed a significant increase in the value of writing skills in accordance with the indicators in the Tarigan theory in Indonesian language learning. In addition to improving writing skills, students are able to be active in learning and creative thinking. Proving this strategy has a positive impact on students to be more confident in themselves.